Simultaneous removal of lead, cadmium, and arsenic Ions from bivalve species using adsorption method - S. N.I.Syed, Najamuddin; Nurasmat, Mohd Shukri; Nur Fatien, Muhamad Salleh; Wan Nazwanie, Wan Abdullah; Norshahidatul Akmar, Mohd Shohaimi; Ahmad Zamani, Ab Halim; Nor Hakimin, Abdullah (Institute of Physics, 2022)
Bivalve such as blood cockle (Tegillarca granosa) feeds by filtering the suspended particle in water including heavy metals and eventually accumulate in the fleshes. Bivalve contaminated with heavy metals might be consumed by human which later could have been exposed to heavy metals toxicity. Therefore, this study was conducted to investigate the effectiveness of adsorption process towards the removal of lead (Pb), cadmium (Cd), and arsenic (As) ions from T. granosa. The findings found that the initial concentration of Pb and As in T. granosa exceeded the permissible limits set by WHO. To remove heavy metals from T. granosa, an adsorption procedure was carried out using lemon and mango peels as natural waste adsorbents. The presence of hydroxyl and carboxylic functional groups in mango and lemon peels was shown in FTIR spectra, which aided in the enhancement of the adsorption process. A series of tests were performed using various parameters such as dosage adsorbents, contact of time, and temperature of reaction. The highest removal percentages of Pb, Cd, and As in T. granosa using lemon peels were 59.65%, 88.89%, and 67.54% respectively. Meanwhile, the maximum removal from T. granosa using mango peels were 70.18% for Pb, 100% for Cd, and 84.71% for As. In conclusion, the adsorption process was effective in removing Pb, Cd, and As in T. granosa. Whereas both lemon peels and mango peels have ability to become effective naturals waste adsorbent in the adsorption process.